1999
DOI: 10.1021/jp990061n
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Interfacial Tension of a Phase-Separated Colloid−Polymer Suspension

Abstract: We studied the interfacial tension between coexisting colloid-rich and polymer-rich fluid phases in a phaseseparated colloid-polymer mixture. First, the location of the fluid-fluid binodal and the tie lines between the coexisting phases were determined using a recently proposed method that only requires the volumes of the coexisting phases as input. The spinning drop method was used to determine the very low interfacial tension between the coexisting phases. We also used the dynamics of the breakup process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
152
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(172 citation statements)
references
References 39 publications
17
152
3
Order By: Relevance
“…This breaking thread method was used to measure the interfacial tension by the determination of the breakup growth rate of an elongated liquid drop in the absence of an overall flow field. In our previous experiments, 8 however, the final rotational speed could not be reduced to zero as it was needed to balance the gravitational force on the droplet. It was observed that the breakup velocity depends also on the final rotational speed.…”
Section: R(z)mentioning
confidence: 99%
See 2 more Smart Citations
“…This breaking thread method was used to measure the interfacial tension by the determination of the breakup growth rate of an elongated liquid drop in the absence of an overall flow field. In our previous experiments, 8 however, the final rotational speed could not be reduced to zero as it was needed to balance the gravitational force on the droplet. It was observed that the breakup velocity depends also on the final rotational speed.…”
Section: R(z)mentioning
confidence: 99%
“…The interfacial tension in a colloid-polymer suspension, phase separated into a colloidal-gas phase and a colloidal-liquid phase, is very low, on the order of 1-10 µN/m and has recently been studied experimentally [7][8][9] and theoretically. [10][11][12] In the experiments, the interfacial tension was measured with the spinning drop method, which is appropriate to measure such low interfacial tensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 2 we compare them for the case Á 2 =Á 1 = 11:6 the value that applies to our experiments [1].…”
Section: The Instability Of a Liquid Cylindermentioning
confidence: 99%
“…Recently we studied the interfacial tension between coexisting phases in a phaseseparated colloid-polymer mixture [1,2]. A crude estimate of the interfacial tension is given by the simple scaling relation [3,4].…”
Section: Introductionmentioning
confidence: 99%